(untitled) (Scientific journal of the Fergana State University, 2025)
M.Y.Lermontov, as a great connoisseur of the Caucasus, was very sensitive to the selection of material for his works. He studied local languages, personally tried to get acquainted with all the traditions and customs of the local population. M.Y.Lermontov can be called a kind of bridge of Russian literature, which was able to unite the Caucasus and Russia, at least within the framework of literary works. This article examines and analyzes the texts of M.Y.Lermontov’s works where oriental linguistic stylization was used.